1986
DOI: 10.1007/bf01310882
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation and inhibition of African swine fever virus by monoolein, monolinolein, and ?-linolenyl alcohol

Abstract: Monoolein, monolinolein and (most strongly) gamma-linolenyl alcohol inactivate ASF virus and inhibit its replication in Vero cells at 25 micrograms/ml while at 10 micrograms/ml no inactivation occurs but inhibition of replication in tissue culture is observed. This suggests two possibly different action mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 5 publications
(4 reference statements)
0
12
0
Order By: Relevance
“…These acids also play important roles in immunity since arachidonic acid is the immediate precursor of the eicosaonoids, the family of biologically active substances which includes the prostaglandins and the leukotrienes. Finally, both unsaturated and saturated fatty acids may inactivate certain viruses in vitro and inhibit their replication in vivo (23).…”
mentioning
confidence: 99%
“…These acids also play important roles in immunity since arachidonic acid is the immediate precursor of the eicosaonoids, the family of biologically active substances which includes the prostaglandins and the leukotrienes. Finally, both unsaturated and saturated fatty acids may inactivate certain viruses in vitro and inhibit their replication in vivo (23).…”
mentioning
confidence: 99%
“…Such a relation was similar to the saturated monoacyl trehalose, maltoses and sucroses [23], and the 6-O-acyl mannose and fructose [26]. 4.2 Effect of unsaturated degree of the acyl chain on CMC and γ CMC The degree of unsaturation in the acyl chain also affected the surface properties, while not as obviously as that of the chain length. The CMC was higher with higher degree of unsaturation, while the γ CMC was almost same (Fig.…”
Section: Effect Of Acyl Chain Length On Cmc and γ Cmcmentioning
confidence: 80%
“…The health and nutritional benefits of the unsaturated fatty acid esters, such as antivirus and dental care, were also observed [4,13]. Besides, it is reported that the oxidation stability of polyunsaturated fatty acid esters is much more stable than that of PUFAs themselves [14,15].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Conversely, unsaturated fatty acids, such as oleic acid, increase membrane fluidity and diminish the infectivity and hemolytic activity of enveloped animal virus particles. No such effects have been described for non-lipid-enveloped animal virus particles (Kohn et al, 1980;Sola et al, 1986a). Oleic acid (Fig.…”
Section: Oleic Acidmentioning
confidence: 99%